2002
DOI: 10.1016/s0029-7844(02)01656-3
|View full text |Cite
|
Sign up to set email alerts
|

Complications associated with optical-access laparoscopic trocars

Abstract: Optical-access trocars may be associated with significant injuries despite having the ability to visualize tissue layers during insertion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
20
0
2

Year Published

2006
2006
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(23 citation statements)
references
References 3 publications
1
20
0
2
Order By: Relevance
“…In fact, as suggested by Sharp et al [11], the complication rate may be much higher and underreported in the literature. They cited an extensive analysis of databases (MDR and MAUDE) maintained by the Food and Drug Administration (FDA) for tracking adverse medical events, and found 79 cases of either trocar-related viscus or vascular injuries (33% involved the Optiview) not reported in the medical literature.…”
Section: Discussionmentioning
confidence: 86%
“…In fact, as suggested by Sharp et al [11], the complication rate may be much higher and underreported in the literature. They cited an extensive analysis of databases (MDR and MAUDE) maintained by the Food and Drug Administration (FDA) for tracking adverse medical events, and found 79 cases of either trocar-related viscus or vascular injuries (33% involved the Optiview) not reported in the medical literature.…”
Section: Discussionmentioning
confidence: 86%
“…This port was designed to progressively visualize the different layers of the wall being cut by the use of a blade during placement. Serious life-threatening complications have been reported (6). We stopped the use of this port and chose an open approach to insert the first port.…”
Section: Discussionmentioning
confidence: 99%
“…Within the 380 right hernia repairs, 91 had undergone a previous appendectomy(6). The operative time averaged 45 minutes for unilateral repairs and 71 minutes for bilateral repairs (range, 15-270 minutes).…”
mentioning
confidence: 99%
“…Even if this is certainly not true in laparoscopic bariatric surgery, laparoscopic bariatric procedures may be more accident prone during trocar placement due to the thicker abdominal wall and larger amount of visceral fat [9]. The visual entry system may represent an advantage over traditional trocars, as it allows a direct view entry, but this advantage has not been fully explored [5,10]. While other authors have reported few or no complications with the bladeless optical trocar, even in the bariatric population [3,4,9,11], to our knowledge, this is the first report of a bladed optical trocar used for peritoneal entry prior to abdominal insufflation.…”
Section: Discussionmentioning
confidence: 99%